EFFECT OF THE APPLICATION OF ACETAZOLAMIDE SOAKED CONTACT-LENSES ON INTRAOCULAR-PRESSURE OF RABBITS - (:unkn) unknown (KLUWER ACADEMIC PUBL, 1992)
Topical application of acetazolamide has no known effect on intraocular pressure (IOP). We tried to detect the hypotensive effect on IOP of acetazolamide soaked onto soft contact lenses (CL). We applied CLs soaked in either 1%, 3%, or 5% acetazolamide solution onto one eye of 29 rabbits while the contralateral eye served as a control. There was an average 32% reduction of IOP amongst all acetazolamide applied eyes, and an average 19% reduction of IOP amongst all control eyes. Amongst the 1% acetazolamide-CL applied eyes there was a mean 37% reduction of IOP, amongst the 3% acetazolamide-CL applied eyes a mean 36% reduction, amongst the 5% acetazolamide-CL applied a mean 30% reduction, and a mean 19% reduction in control eyes. The longest period of IOP reduction followed the application of 1% acetazolamide-CLs, probably owing to improved drug corneal penetration at this concentration. Our results reveal that the application of acetazolamide soaked soft CLs has a significant hypotensive effect on IOP in both the applied and contralateral control eyes of rabbits.
Keywords: ACETAZOLAMIDE; CARBONIC ANHYDRASE INHIBITOR; INTRAOCULAR PRESSURE; SOFT CONTACT LENSES; CARBONIC-ANHYDRASE INHIBITOR; MK-927